Neutrophil-to-Lymphocyte Ratio in Neonates: A Predictor of Early-Onset Neonatal Sepsis - Nguyen, Thi Thanh Binh; Tong, Khanh Linh; Linh, Hoang Mai (Journal of Pediatric Infectious Diseases, 2024)
Objective Early-onset neonatal sepsis (EOS) is a common cause of mortality in the neonatal period. The purpose of the study was to determine the value of the neutrophil-to-lymphocyte ratio (NLR) in the early diagnosis of EOS.Methods This was a prospective cross-sectional study. A total of 102 newborns with early-onset infection (EOI) were enrolled within the first 72 hours of life in the neonatal intensive care unit of a tertiary referral hospital, the largest pediatric center in central Vietnam.Results Among 102 newborns, 32 were identified as having EOS, while the remaining 70 were classified as EOI. The median NLR value in the EOS group (2.7 [2.0–5.6]) was statistically significantly higher than that in the EOI group (1.7 [1.0–2.4], p < 0.05). The NLR demonstrated a moderate ability to discriminate between EOS and EOI with the area under the curve (AUC) of 73.6% (p < 0.05). An NLR cut-off of 1.87 was found to be optimal, with a sensitivity of 84.4%, a specificity of 60.0%, a positive predictive value of 49.1%, and a negative predictive value of 89.4%. The combination of NLR and C-reactive protein demonstrated the best performance in predicting EOS, with the AUC of 85.3% (95% confidence interval: 76.9–91.5).Conclusions This study suggests that NLR can be used as an additional diagnostic marker, alongside C-reactive protein, for the early diagnosis of EOS.
Keywords: early-onset sepsis; neonates; neutrophil-to-lymphocyte ratio